Pengembangan Sistem Informasi Nilai Ujian Online dengan Gammu - Rico Andrian; Didik Kurniawan; RA Dina Nia Pratiwi (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2015)
School information is very important for associating parents and school. Information about student at school such a test score as a means of academic activity is very important for parents to know. Usually test score information is only informed when report is given to parents. The system that we developed is used to report student test score via SMS Gateway and working properly. The SMS Gateway system is created using a MySQL database, Gammu and PHP.